Surface induced bulk modifications of amorphous carbon nitride films by post-deposition oxygen and hydrogen plasma treatment - Miyajima, Y.; Nitta, S.; Silva, S.R.P.; Zeze, D.A. (Thin solid films, 2005)
Hydrogen-free amorphous carbon nitride films (a-CN x ), prepared at room temperature by radio frequency (RF) magnetron sputtering under a 99.999% argon atmosphere, are irradiated with hydrogen (a-CN x :H) or oxygen (a-CN x :O) plasma to prepare layer-by-layer amorphous carbon nitride films (a-CN x :LL). a-CN x :LL are prepared by growing cyclically thin layers of a-CN x by reactive radical sputtering of graphite, which is then subject to hydrogen or oxygen plasma treatment, with the process repeated to build up thicker layers. The analysis of the structural properties and surface morphology of these films by X-ray photoelectron spectroscopy and atomic force microscopy shows that the chemical composition and microstructure are strongly dependent on the post-deposition plasma treatment. The refractive index and Tauc band gap indicate that the optical properties these films can be altered by post-deposition plasma treatment only, without resorting to annealing due to the diffusion of oxygen/hydrogen that occurs between a-CN x layers.